Behind opening doors: problems of translation awareness in a linguistically and culturally homogenous Central European society - Pisarska, Alicja (Scripta Neophilologica Posnaniensia, 2018)
Behind opening doors: problems of translation awareness in a linguistically and culturally homogenous Central European society